School Management At Sma Negeri 1 Gebog Kudus - Johan Sutarjo (Journal Of Social Science (JoSS), 2023)
Based on the results of research on "School Management at SMA Negeri 1 Gebog Kudus", school management, which is a way of behavior in managing schools so that the process in learning can run well, is also implemented at SMA Negeri 1 Gebog Kudus. This school has a wide environment, and also the management of school management is also good in the context of teaching and learning activities. The determination of the research location is at SMA Negeri 1 Gebig Kudus which is a school with accreditation A. Research objectives are specifically formulated: To find out and explain the school profile of SMAN 1 Gebog Kudus, To know and explain the management of the school curriculum of SMAN 1 Gebog Kudus, To know and explain the management of students at SMAN 1 Gebog Kudus,  To know and explain personnel management at SMAN 1 Gebog Kudus school, To know and explain the finances in the school of SMAN 1 Gebog Kudus, to know and explain the management of public relations in the school of SMAN 1 Gebog Kudus, to know and explain the infrastructure in the school of SMAN 1 Gebog Kudus, and to know and explain the management of special services in the school of SMAN 1 Gebog Kudus. The implementation of school management at SMAN 1 Gebog Kudus has met good standards, this can be seen from the performance of professional educators in KBM. This study has used a descriptive study, & qualitative approach. In this study, observations have been made in the form of data collection techniques in several ways, including: observation, & interview.